PATTERNS OF RESPONSES TO COMPLIMENTS ON PHYSICAL APPEARANCE IN SUNDANESE WOMEN - Refdi Akmal (University of Kuningan, 2013)
Abstract: Complimenting as a speech event has been one of the major areas on which linguists have focused their attention and drawn insights into the phenomenon of linguistic politeness in the last two decades (Zanrong 2004). Some previous research – among others are by Davis (2008); Heidari (2009); Matsuoka (2009) – revealed that gender give rise variations of strategies on compliment responses (CR). This paper examines Sundanese women responses to compliments on appearance addressed by the same and different gender. The research applied Naturalized Role Play method in collecting the data by observing the way of 68 women giving response to the compliment addressed on their physical appearance. The respondents were native Sundanese women living around Bandung. The study found that most women respond differently to compliments addressed to them by women and by men. This study also reveals that most of them considered the compliments – particularly when addressed by men – as a way of either maintaining social hospitalities or joking, and thus, the speech acts of compliments appear more to be a way of consolidating solidarity among them. Keywords: politeness, compliments, patterns of response